Corynebacterium jeikeium Dormant Cell Formation and Photodynamic Inactivation - Shleeva, Margarita; Savitsky, Alexander; Kaprelyants, Arseny (Frontiers in Microbiology, 2020)
Pathogenic non-spore forming bacteria enter a dormant state under stressful conditions, which likely allows them to acquire resistance to various antibiotics. This work revealed the efficient formation of dormant 'non-culturable' (NC) Corynebacterium jeikeium cells in stationary phase upon gradual acidification of the growth medium. Such cells were unable to form colonies and existed in a prolonged stationary phase. At an early stage of dormancy (approximately 14 d post-inoculation), dormant cells are able for resuscitation in liquid medium. However, those stored for long time in dormant state needed addition of supernatant taking from active C. jeikeium cultures for successful resuscitation. NC cells possessed low RNA synthesis and significant tolerance to antibiotics (rifampicin and vancomycin). They also accumulated free porphyrins, and 5-aminolevulinic acid addition enhanced free porphyrin accumulation which makes them potentially sensitive to photodynamic inactivation (PDI). PDI of dormant bacteria was accomplished by exposing cells to a 565 nm wavelength of light using a SOLIS-4C light-emitting diode for 60 min. This revealed that increased porphyrin concentrations were correlated with elevated PDI sensitivity. Results shown here demonstrate the potential utility of employing PDI to minimise levels of dormant, persistent corynebacteria and the C. jeikeium dormancy model developed here may be useful for finding new drugs and techniques for combatting persistent corynebacteria.